Methods in psychological research - Evans, Annabel (Sage Publications, 2008)
Written in a clear compelling manner, Methods in Psychological Research is THE only text that takes readers through the research process from reading the literature to writing up a research report. It is pedagogically driven, interactive, and highly applied to engage and motivate students who are taking what is often considered to be a “drudge” requirement. Authors Annabel Ness Evans and Bryan J. Rooney present this brief and basic introduction to research methods in psychology in a relaxed style, at a moderate level of detail, and with a rich mix of pedagogy to encourage students from a variety of backgrounds and academic preparation and to help connect students to the material. The authors offer an applied approach, emphasizing doing research with simple in-text exercises that are more interactive than those found in most methods textbooks. They also provide examples of real psychology research, both from the research literature and, uniquely, from student research projects. This friendly and supportive presentation of the basics conveys to students the excitement and fun of the research enterprise and involves them in doing research rather than just memorizing another term for an exam.